2008
DOI: 10.1038/jcbfm.2008.24
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects of Statin and Dipyridamole on Cerebral Blood Flow and Stroke Protection

Abstract: Recent studies suggest that dipyridamole (DP) may exert stroke protective effects beyond platelet inhibition. The purpose of this study is to determine whether statin and DP could enhance stroke protection through nitric oxide (NO)-dependent vascular effects. Mice were pretreated with DP (10 to 60 mg/kg, q 12 h, 3 days) alone or in combination with a statin (simvastatin; 0.1 to 20 mg/kg per day, 14 days) before transient intraluminal middle cerebral artery occlusion. Although simvastatin (1 mg/kg per day, 14 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Is it possible that some form of endothelial protection may contribute to potential beneficial properties of dipyridamole in cerebral ischemia? A recent study demonstrated that subtherapeutic doses of dipyridamole combined with simvastatin were able to exert additive NO-dependent vascular effects on a mouse stroke model with increased cerebral blood flow, leading to decreased stroke volume and improved neurologic outcomes [33]. Further investigations appear warranted to truly dissect these neurovascular pathways of dipyridamole in the context of stroke and cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Is it possible that some form of endothelial protection may contribute to potential beneficial properties of dipyridamole in cerebral ischemia? A recent study demonstrated that subtherapeutic doses of dipyridamole combined with simvastatin were able to exert additive NO-dependent vascular effects on a mouse stroke model with increased cerebral blood flow, leading to decreased stroke volume and improved neurologic outcomes [33]. Further investigations appear warranted to truly dissect these neurovascular pathways of dipyridamole in the context of stroke and cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that dipyramidol augmented the neuroprotective effects of statins in an eNOS-dependent way (Kim et al, 2008). The putative mechanism involves an increase in eNOS S1177 phosphorylation, as demonstrated in spontaneously hypertensive rats (Oyama et al, 2011) based on the reduction in postischemic brain damage following pretreatment with PDE inhibitor cilostazol.…”
Section: Phosphodiesterase Inhibitorsmentioning
confidence: 99%
“…Dipyridamole, a phosphodiesterase-5 inhibitor, has been shown to decrease the cerebral infarct size, and the combination of subtherapeutic doses of statin and dipyridamole increased eNOS activity and cerebral blood flow and reduced infarct volume. 30 In addition to these phosphodiesterase inhibitors, it has been reported that several modalities, such as statin, angiotensin II type 1 receptor blocker, Rho kinase inhibitor, and L-arginine, upregulated eNOS expression, increased eNOS activity, and inhibited oxidative stress. 3,6,8,[31][32][33] All of these modalities increase endothelium-derived NO availability and have been shown to enhance CBF, resulting in neuroprotection after cerebral ischemia.…”
mentioning
confidence: 99%